PENGARUH KOMPENSASI DAN MOTIVASI KERJA TERHADAP KINERJA PEGAWAI YANG DIMEDIASI OLEH KEPUASAN KERJA (Studi pada PT. Bank Rakyat Indonesia (Persero) Tbk. Wilayah Semarang Metro) - 11.52.02.0070, Gita Febriana Sari (Jurnal Mahasiswa Pasca Sarjana, 2013)
This study aimed to examine the effect of compensation and motivation on employee performance is mediated by job satisfaction in employees of PT .Bank Rakyat Indonesia (Persero)Tbk Semarang Metro Area. The population in this study was the BRI bank employees 300 people, where sampling technique with purposive sampling criteria have become a permanent employee minimum term of 5 years, in order to obtain a total sample of 103 people. Testing the research instrument to 40 items using validity by factor analysis with Alpha Chrombach reliability test, whereas data analysis techniques using multiple linear regression.The study found that the direct effect of compensation on performance. Compensation is formed especially in the form of material and social compensation, namely the existence of insurance coverage, a bonus in the achievement of targets, the promotion of an employee, and the comfort of working space. As for the performance achieved the employees in the form of quantity of work, which is achieved through teamwork targets, the division of labor, and complete the work in accordance with the procedure. Job satisfaction is not able to mediate the effect of compensation on employee performance and motivation PT. Bank Rakyat Indonesia because the results obtained are not significant. Keywords: compensation, motivation, satisfaction, performance